Peran, Hambatan, dan Tantangan Polisi Kehutanan di Wilayah Kerja RPH Pesapa - Nasrullah, Nasrullah (CV. Social Politic Genius (SIGn), 2023)
This research examines the role of the Forestry Police and the obstacles and challenges they face in combating illegal logging in the Pesapa FMR’s Work Area. Employing empirical research methods, it utilizes primary and secondary data from April to June 2023 in Batulappa Sub-district, Pinrang Regency, Indonesia. The study then analyzes the acquired data qualitatively to describe the problem and answer the research objectives. The findings reveal that the Forestry Police in the Pesapa FMR’s Work Area encounter several obstacles and challenges in executing forest protection. These obstacles include limited functional officers and equipment, the extended area of the protection forest requiring safeguarding, and the Batulappa community’s lack of understanding about forest boundaries and functions. Another emerging factor is the suboptimal law enforcement by the Forestry Police, especially in illegal logging cases involving local communities. Therefore, the Head of the TIU of Sawitto FMU is recommended to increase the number of functional officers and ownership of Forestry Police equipment in the Pesapa FMR’s Work Area. Furthermore, a continuous education program on the importance of forest conservation and the dangers of illegal logging for the Batulappa community must also be implemented. The Local Government must also seek alternatives for agricultural and plantation land use. Lastly, the Forestry Police must show a more substantial commitment to handling illegal logging cases, reinforcing the Government’s dedication to forest protection.